The impact of dimethylformamide on the synthesis of graphene quantum dots derived from graphene oxide - Khuong T. Truong; Thach H. Pham; Khai V. Tran (Chimica Techno Acta)
Graphene quantum dots (GQDs) have garnered immense interest in recent years due to their unique optical, electrical, and chemical properties, making them promising candidates for various applications in optoelectronics, bioimaging, and sensing. However, enhancing the control over the size, surface chemistry, and optical properties of GQDs remains a significant challenge. In this study, a novel recipe was proposed to successfully synthesize various GQDs via a typical solvothermal process, which has proven to be a versatile and scalable approach. In addition to the main ingredient – graphene oxide suspension, dimethylformamide (DMF) and hydrogen peroxide serving as a cutting agent were added to the reaction mixture. This synthesis method was found to be more promising than the reference one in which DMF was replaced by double distilled water. Through systematic experimentation, we demonstrated that the addition of DMF enables the successful GQD production over a wider range of reaction times; hence, the UV absorption band and photoluminescence properties of GQDs can be better adjusted. The dependence of photoluminescence on the excitation wavelength was observed in the as-prepared materials as they were excited with a range of wavelengths from 360 to 480 nm. The obtained insights not only advance our understanding of GQD synthesis but also open up avenues for tailoring their properties for specific applications.